Factors Affecting Financial Performance in the Banking Sector Listed on the Indonesia Stock Exchange - Silalahi, Elli Dayanti; Siallagan, Hamonangan; Dolok Saribu, Ardin (Universitas Muhammadiyah Tangerang, 2025)
In the context of Indonesia's growing economy, a deep understanding of the factors that affect the financial performance of banks is essential to improve financial system stability and public trust. This study aims to analyze the influence of CAR, NPL, BOPO, and LDR on the financial performance of banks listed on the Indonesia Stock Exchange for the 2021-2023 period, with ROA as a proxy for financial performance. Using a quantitative approach, annual financial statement data is analyzed through multiple linear regression. The results of the study showed that BOPO had a significant effect on ROA, while NPL showed a significant negative impact. Meanwhile, CAR and LDR showed no significant influence. These findings make a practical contribution to banking management in optimizing the management of operational costs and credit risks, as well as being a reference in strategic decision-making. The novelty of this study lies in its comprehensive approach in analyzing the interaction of the four main financial ratios in the post-pandemic period (2021-2023), using actual data that has not been widely explored in the context of Indonesian banking, as well as providing the latest empirical evidence on the dominant influence of operational efficiency (BOPO) over other factors.